Coumarins: Spectroscopic measurements and first principles calculations of C4‐substituted 7‐aminocoumarins. (3rd May 2018) - Singh, Shraddha; Begoyan, Vagarshak V.; Tanasova, Marina; Waters, Kevin; Seel, Max; Pandey, Ravindra
Abstract: Coumarins are widely applied in sensing devices due to their diverse fluorescence properties. In this paper, we consider the C4‐substituted 7‐aminocoumarins to investigate the structure‐property relationship via examining the effect of the various substitutions on their optical properties. Absorption and fluorescence measurements together with time‐dependent density functional theory calculations are described. We find that the significant red shift in the fluorescence spectra is associated with the cyclic carbonyl group of coumarins due to a substantial increase in the dipole moment in the photoexcited state. The apparent correlation between experimental and calculated results provides an atomistic‐level insight into the role of the functionality at the C4 of coumarins and sets the basis for using computational analysis to predict the fluorescence properties of coumarins. Abstract : The computational analysis of the ground state and excited state properties of the fluorophores of the coumarin family in the attempt of predicting absorption and fluorescence properties is described. The experiment and theory correlate well with the overall impact on the absorbance, and emission maxima by the substitution at the C4‐position of the analyzed focused coumarin library, providing the theoretical basis for tuning coumarin fluorescence.